1992
DOI: 10.1002/cne.903230303
|View full text |Cite
|
Sign up to set email alerts
|

Sylvian fissure morphology and asymmetry in men and women: Bilateral differences in relation to handedness in men

Abstract: The anatomy of the sylvian fissure in the human brain was studied to develop reliable criteria for anatomical landmarks of the posterior part of the fissure for use in its definition and measurement; to quantify right-left asymmetries in segments of the sylvian fissure; to assess whether any anatomical features are associated with hand preference (selected as one index of hemispheric functional asymmetry); and whether structure-function relationships are similar in men and women. A sample of 67 brain specimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
136
1
4

Year Published

1993
1993
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(153 citation statements)
references
References 42 publications
12
136
1
4
Order By: Relevance
“…While Witelson & Kigar (1992) suggest that anatomical asymmetry is associated with functional asymmetry, given that the majority of men are right-handed.…”
Section: Discussionmentioning
confidence: 99%
“…While Witelson & Kigar (1992) suggest that anatomical asymmetry is associated with functional asymmetry, given that the majority of men are right-handed.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, corresponding to the volumetric analysis, all heritability estimates in the VBM analysis were calculated from ACE models. Handedness was added as additional covariate in the voxel-wise analysis (measured with the Edinburgh Handedness Inventory [Oldfield, 1971]), since handedness can have subtle effects on, for example, asymmetry of the motor cortex [Amunts et al, 2000;Hervé et al, 2006] and sylvian fissure [Witelson and Kigar, 1992]. The critical v 2 -value for P < 0.05 after correction for multiple comparisons was 17.7 for WM density and 20.5 for GM density (df 5 1), according to the false discovery rate [Genovese et al, 2002].…”
Section: Genetic Analysesmentioning
confidence: 99%
“…Nonetheless, empirical evidence supporting presence of greater structural asymmetries in men compared to women are relatively well replicated in perisylvian brain regions (Wada et al, 1975;Witelson and Kigar, 1992;Kulynych et al, 1994;Good et al, 2001;Knaus et al, 2004), where sex effects have also been shown to be influenced by handedness (Witelson and Kigar, 1992;Jancke et al, 1994;Kulynych et al, 1994). Some evidence also suggests that sex influences hemispheric torque where greater degrees of right-frontal and leftoccipital width asymmetries have been observed in men compared to women using CT data (Bear et al, 1986).…”
Section: Sex Effectsmentioning
confidence: 99%